Pulmonary and hepatic effects after low dose exposure to nanosilver: Early and long-lasting histological and ultrastructural alterations in rat. (2019) - Roda, E; Bottone, MG; Biggiogera, M; Milanesi, G; Coccini, T
Highlights: Low AgNPs dose caused in vivo toxic effects both at portal entry and distant organ. Lung and liver tissues were damaged in Nanosilver-instilled rat. Early and long-lasting histological and ultrastructural alterations were detected. Overall pulmonary injury was more striking compared to hepatic outcomes. Abstract: Although environmental airborne silver nanoparticles (AgNPs) levels in occupational and environmental settings are harmful to humans, the precise toxic effects at the portal entry of exposure and after translocation to distant organs are still to be deeply clarified. To this aim, the present study assessed histopathological and ultrastructural alterations (by means of H&E and TEM, respectively) in rat lung and liver, 7 and 28 days after a single intratracheal instillation (i.t) of a low AgNP dose (50 microg/rat), compared to those induced by an equivalent dose of ionic silver (7 microg AgNO3/rat). Lung parenchyma injury was observed acutely after either AgNPs or AgNO3, with the latter compound causing more pronounced effects. Specifically, alveolar collapse accompanied by inflammatory alterations and parenchymal fibrosis were revealed. These effects lasted until the 28th day, a partial pulmonary structure recovery occurred, nevertheless a persistence of slight inflammatory/fibrotic response and apoptotic phenomena were still detected after AgNPs and AgNO3, respectively. Concerning the liver, a diffuse hepatocyte injury was observed, characterized by cytoplasmic damage and dilation of sinusoids, engulfed by degraded material, paralleled by inflammation onset. These effects already detectable at day 7, persisting at the 28th day with some attenuations, were more marked after AgNO3 compared to AgNPs, with the latter able to induce a ductular reaction. Altogether the present findings indicate toxic effects induced by AgNPs both at the portal entry (i.e. lung) and distant tissue (i.e. liver), although the overall pulmonary damage were more striking compared to the hepatic outcomes.